The influence of entrepreneurial skills, environmental support and motivational factors on entrepreneurial intention - Ibrahim Siam, Ibrahim Mahmoud; Abu Bakar, Lily Julienti; Alshuaibi, Mohammad Said Ibrahim; Alshuaibi, Ahmad Said (2015)
This study exploits Theory of Planned Behaviour to capture the entrepreneurial intention among students in Universiti Utara Malaysia (UUM).It was revealed that entrepreneurial skills, environmental support and motivational were the key factors which positively related with entrepreneurial intention among the students. Self-administered questionnaires were distributed to the students of Bachelor in Business Administration (BBA) and Bachelor of Entrepreneurship (BEnt) students in UUM in order to identify their entrepreneurial intention and the influence factors.A stratified sampling technique was used to among 200 students who participated in the study.Generally, results show that entrepreneurial skills; environmental support and motivational factors are significantly related to the entrepreneurial intention.